Data Mining and Analysis of Management Theory on the Emotional Recognition of Students' Physical Fitness Improvement. (9th May 2022) - Fan, Jingang; Yu, Le; Liu, Jiabao
Abstract : The improvement of the economic level has brought earth-shaking changes to people's living standards. However, with the improvement of living standards, the pace of life is also accelerating, people's physical and psychological pressure has also increased sharply, and people's physical and mental health problems are also increasing. As an important threshold for talent training schools, real-time monitoring of students' physiques, and effective training of students' physical fitness, so schools need to strengthen the scientific management of students' work and rest and exercise according to management theory. To better pay attention to the correlation between students' physical fitness and psychological emotions, this paper designs a data analysis system for students' physical health based on data mining, analyzes the improvement of students' physical fitness under health management, and then identifies students' emotions according to this to observe the impact of students' physical fitness improvement on emotional changes, so as to effectively improve students' physical health level and mental health level. The experimental results of the research system in this paper show that the improvement of students' physical fitness can promote students' emotional recognition, and its accuracy can be improved by at least 2%, and various types of emotions can be accurately identified, indicating that changes in students' physical fitness have a certain impact on student emotions.